Instrumentação e controle de uma estação de tratamento de água - Selma Capanema de Barros (2004)
Capanema, S. P. Instrumentação e Controle do Processo de Coagulação em uma Estação de Tratamento de Água. Belo Horizonte, 2004. Dissertação (Mestrado) Escola de Engenharia da Universidade Federal de Minas Gerais. That work presents the study developed in the Station of Treatment of Water of Rio of the Old ones- ETA, of property of COPASA- Company of Sanitation of Minas Gerais (New Lima,Metropolitan Area of Belo Horizonte) during the period of July of 2002 to June of 2004, to evaluate the use of analytical instrumentation for ends of control of the coagulation process and to develop models that, associates to control techniques, they can be used to make theautomatic control of the dosage of clotting. For so much, they were made partnership contracts with traditional manufacturers of applied analytical instrumentation to the area of sanitation and accomplished comparative analyses of the answer of the several instruments. Defined the most appropriate instruments for the quality of the water of Rio of the Old ones, it was built a database that made possible, using methods no parametric, through graphs of crossed correlation, to evaluate the relationship among the variables of the process. Starting from the result of this analysis, of the operational methods adopted in ETA andbibliographical references was done the identification of the most relevant variables for development of the models. They were identified as variables that influence the coagulation process the flow of waterflowing to ETA (rude water), the turbidity and the true color of the rude water and the coagulation pH. Another varied were appraised such as conductivity and temperature of the rude water and type of clotting. The conductivity presented a narrow variation strip, between 32 and 40 mS/cm, and also low correlation with the other variables. The coagulant type was not altered during the period that that work was developed, being the alterations linked to supply contracts done by COPASA. In ETA salts are used the base of iron (ferric chloride or chlorinated ferrous sulfate). During the period of construction of the database, it was madeuse of ferrous sulfate chlorinated in the concentration of 17,5 mg/L Fe2O3 and density of 1,5 g/L. the temperature of the rude water stayed practically constant, with medium value of 22 °C. Defined the variables, several models were developed being used topologies different from Artificial neural networks, with the objective of obtaining a model to represent the behavior of the operator when controlling the coagulant dosage and a model to make the prediction of the turbidity of the decanted water.Initially, several models were developed to make the prediction of the turbidity of the decanted water, using MATLAB. Those models were implemented in a program in programming language C++. Using the available automation resources in ETA, the program was connected to a supervisório, turning possible the acquisition of the values of the entrance variables and the graphic registration of the exit of each one of the models on line. To identify the operator's behavior he/she occurred procedure similar to that for the prediction of the turbidity of the decanted water. Those programs can, now, to be used by the operator to orientate their actions, when adjusting the coagulant dosage, compensating the time killed of the plant, through the prediction of the turbidity of the decanted water.